CASHCLASS AS AN EFFECTIVE AND PRACTICAL CLASSROOM CASH FINANCIAL MANAGEMENT APPLICATION FOR STUDENTS IN AN EDUCATIONAL ENVIRONMENT - Andika Isma; M. Miftach Fakhri; A. Nurul Uswatun Hasanah; Nurikhlas Noerpa Gunawan; Andi Naila Quin Azisah Alisyahbana; Della Fadhilatunisa (Jurnal Media Elektrik, 2024)
This article discusses a class cash financial management application designed to facilitate a class financial administrator in managing cash finances in an educational environment. This application provides features such as recording income and expenses, tracking transactions, automatic financial reports. The purpose of this application is to improve the efficiency, accuracy, and affordability of classroom financial information. Another advantage of this class cash financial management application is its ability in the reporting process. This application can generate automatic financial reports that can be customized as needed. This is very useful for reporting purposes to the authorities or for audit purposes. With this application, the process of preparing financial reports becomes faster, more accurate, and more efficient. Overall, this article discusses a class cash financial management application that provides benefits in financial management efficiency, easy access to information, and reporting capabilities. This application can be a useful tool for class financial administrators such as class treasurers in managing class cash finances more effectively and efficiently. The test results of this CashClass application show that this CashClass application functions properly in accordance with the requirements and expectations that have been set.